Structural Equation Modelling Analysis of Improving Teachers’ Teaching Creativity:The Role of Professional Identity and Emotional Intelligence - Muhammad Fahmi Johan Syah; Naufal Ishartono; Agus Susilo; Nurul Latifatul Inayati; Sharul Effendy Janudin; Mahaliza Mansor; Salma Rahmadhani; Alifa Salsabila; Hanifah Tria Intan Jelita (FKIP Universitas Lampung, 2024)
Structural Equation Modelling Analysis of Improving Teachers' Teaching Creativity: The Role of Professional Identity and Emotional Intelligence. Objective: The study aimed to examine a comprehensive structural model comprising three variables namely teaching creativity, emotional intelligence, and professional identity. Methods: The study involved 170 prospective teachers enrolled in teacher professional education programs in Indonesia by using a simple random sampling technique. Data were collected online using instruments adapted from previous research. The data were analysed by using covariance-based Structural Equation Modelling (CB-SEM) with the assistance of AMOS. Findings: The findings revealed that the model confirmed a strong relationship among the three variables. Partial regression analysis reveals that emotional intelligence influences professional identity and teaching creativity, while professional identity influences teaching creativity. Nevertheless, the full model analysis revealed a contrary result that emotional intelligence could not directly enhance teaching creativity. Emotional intelligence must be accompanied by a strong professional identity to boost creativity in teaching effectively. These results suggest that professional identity functions as a full mediator in the relationship between emotional intelligence and teaching creativity. Conclusions: Efforts to enhance teaching creativity should focus not only on developing emotional intelligence but also on strengthening professional identity. This identity comprises several components, including cultural knowledge, blending, interpersonal skills, and active engagement in the professional community. Neglecting professional identity may hinder improvements in teaching creativity, even if emotional intelligence is high. Stakeholders should prioritise both aspects to cultivate creative educators. Keywords: teaching creativity, emotional intelligence, professional identity, SEM, teacher.DOI: http://dx.doi.org/10.23960/jpp.v14.i2.202498